Practical implications of "vaccine nationalism": A short-sighted and risky approach in response to COVID-19 - Muhammad Zaheer Abbas (South Centre, 2020)
To end the COVID-19 pandemic and ensure a return of normalcy, an effective and safe vaccine is the best hope. The vaccine nationalism approach, adopted by some countries to gain preferential access to emerging COVID-19 vaccines, poses a threat to the fair and equitable distribution of the potential vaccines across the globe. This research paper critically evaluates the approach of vaccine nationalism and argues that this self-centred political behaviour of leaving others behind is short-sighted, potentially risky, morally indefensible, and practically inefficient in containing the pandemic. This paper highlights why it is important for national governments to support the collaborative and coordinated effort of the COVID-19 Vaccines Global Access (COVAX) facility for the timely development and efficient delivery of potential COVID-19 vaccines. It concludes that an effective response to the current health and economic crisis should be guided by values of international solidarity, multilateralism, equality, and global collaboration. It proposes the adoption of an enforceable global framework to address the concerns arising from the combination of vaccine nationalism and intellectual property exclusivities.
Keywords: 300; Access to Medicines; China; Coronavirus; COVAX Facility; COVID-19; Equality; Health; Intellectual Property; International Solidarity; Multilateralism; Pandemic; Russia; United States (US); Vaccine Nationalism; Vaccines; World Health Assembly (WHA); World Health Organization (WHO)